Low-warpage laminated sheet ceramic and anti-warpage preparation method of laminated sheet ceramic

By improving the stacking method of alumina ceramics and adopting multi-stage program temperature isostatic pressing and sintering processes, the problem of high warpage rate of ceramic sintering is solved, and the extremely low warpage and efficient production process of ceramic products are achieved.

CN119874335AInactive Publication Date: 2025-04-25JIANGSU BREE OPTRONICS CO LTD

Patent Information

Application Number
CN202411883927.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-04-25
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The prior art has problems in improving the sintering warpage of alumina ceramics and affecting the casting effect. Especially after increasing the solid content of casting slurry, it is easy to cause uneven dispersion of components and prone to agglomeration.

Method used

By improving the lamination method of cast green body, multi-stage temperature isostatic pressing and sintering processes are used to ensure that the internal residual stress distribution of ceramic green body is adjusted, thereby reducing the warpage after sintering.

Benefits of technology

The extremely low warpage of ceramic products is achieved, reaching 100% within the proportion of less than side length *0.1%, while avoiding the problems of uneven dispersion and casting effect caused by increasing the solid content of casting slurry.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119874335A_ABST
    Figure CN119874335A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of ceramic material preparation, and particularly discloses low-warpage laminated sheet ceramic and an anti-warpage preparation method of the laminated sheet ceramic. The warping degree of the low-warping laminated sheet ceramic at least accounts for 100% when the warping degree is smaller than side length * 0.1%. According to the anti-warping preparation method of the laminated sheet ceramic, residual stress distribution in a ceramic green body obtained after tape casting is adjusted to the maximum extent in a rotating and oppositely-stacking lamination mode; and meanwhile, the temperature isostatic pressing and sintering processes are synergistically treated by adopting multiple sections of programs, so that the problems of sintering warping, low production yield and the like of the laminated sheet ceramic are efficiently solved at low cost. According to the anti-warping preparation method, the solid content of the tape-casting slurry does not need to be increased, a scheme for improving the warping rate by increasing the solid content in the prior art is avoided, and the defects that dispersion is easy and uneven, the tape-casting effect is affected and the like due to the high solid content can also be avoided due to the low solid content.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of ceramic material preparation, and in particular relates to a laminated thin-sheet ceramic with extremely low warpage, and a warpage-resistant preparation method of the laminated thin-sheet ceramic. Background Art

[0002] Alumina ceramics have significant advantages such as high melting point, small dielectric constant, high volume resistivity, strong resistance to thermal shock and easy availability of raw materials. They are widely used in modern production and life and are developing rapidly.

[0003] Tape casting, an important wet-forming process for producing thin ceramic sheets, involves the preparation of the tape casting slurry, the preparation of the green sheets, the crucial green sheet processing steps of cutting and laminating, and finally, sintering to form the ceramic. However, improper design or operation during the green sheet casting, winding, and cutting processes can easily lead to residual stress within the green sheets, which in turn can cause warping of the alumina ceramic after sintering, seriously compromising the quality of the finished ceramic.

[0004] Currently, there are measures to improve the warpage resistance of thin ceramic sheets, such as Chinese patent application CN118993712A. By adjusting the amount of each component, the solids content of the tape-casting slurry is increased to 65% to 70%, thereby increasing the density of the tape-cast green body and reducing the warpage of the sintered product. However, this method of increasing the solids content of the tape-casting slurry can easily lead to uneven dispersion of the components, easy agglomeration, and poor tape-casting performance due to the excessive solids content.

[0005] Therefore, it has become a top priority to explore other ways to improve alumina ceramics by reducing the sintering warpage during the preparation process to ensure stable product quality. Summary of the Invention

[0006] To address the existing issues of improving ceramic product warpage by increasing the solids content of the tape-casting slurry, which can lead to poor dispersion and compromised tape-casting results, the present invention provides a novel low-warpage laminated ceramic sheet and a warpage-resistant method for preparing such laminated ceramic sheets. This low-warpage laminated ceramic sheet achieves a warpage level of up to 100% within a range of at least 0.1% of the side length. This warpage-resistant preparation method effectively addresses the sintering warpage issue of the laminated ceramic sheet by improving the tape-cast green body lamination method, supplemented by a multi-stage warm isostatic pressing and sintering process.

[0007] The present invention specifically adopts the following technical solutions:

[0008] A low-warpage laminated ceramic sheet, wherein the warpage of the low-warpage laminated ceramic sheet is at least less than 100% of the side length*0.1%.

[0009] Among them, the low-warpage laminated thin-film ceramic is made of a tape-casting slurry with a solid content of 60% to 65% through tape-casting, lamination and sintering; the tape-casting slurry is a mixture of 100 to 120 parts by mass of alumina, 4 to 6 parts by mass of a sintering aid, 0.5 to 1.5 parts by mass of a dispersant, 8 to 14 parts by mass of a binder, 6 to 9 parts by mass of a plasticizer, and 40 to 60 parts by mass of a solvent.

[0010] Furthermore, the sintering aid is a mixture of 1 to 3 parts by mass of calcium carbonate and 1 to 3 parts by mass of silicon dioxide, or a mixture of 1 to 3 parts by mass of calcium oxide and 1 to 3 parts by mass of silicon dioxide.

[0011] Furthermore, the dispersant is selected from polyacrylic acid or ammonium polyacrylate.

[0012] Furthermore, the binder is selected from any one of polyvinyl alcohol, hydroxypropyl methylcellulose, methylcellulose, hydroxyethyl cellulose, and acrylic emulsion.

[0013] Furthermore, the plasticizer is selected from any one of polyethylene glycol, glycerol, and dibutyl phthalate, or a mixture of any two thereof.

[0014] Generally, the solvent is water.

[0015] The present invention also provides a method for preparing a warpage-resistant laminated ceramic sheet, which comprises the steps of:

[0016] S1, preparing a tape casting slurry, and tape casting and cutting the tape casting slurry to obtain a ceramic green body;

[0017] S2, performing a rotationally symmetrical lamination process on an even number of ceramic green sheets to obtain a laminated green body;

[0018] S3. The laminated green body is subjected to multi-stage warm isostatic pressing and multi-stage sintering in sequence to obtain laminated thin-sheet ceramics.

[0019] Specifically, in step S1, the solid content of the casting slurry is 60% to 65%; and the casting slurry is a mixture of 100 to 120 parts by mass of alumina, 4 to 6 parts by mass of a sintering aid, 0.5 to 1.5 parts by mass of a dispersant, 8 to 14 parts by mass of a binder, 6 to 9 parts by mass of a plasticizer, and 40 to 60 parts by mass of a solvent.

[0020] The solid content of the tape casting slurry is the percentage of the total mass of the solid phase powder (specifically, a mixture of alumina and a sintering aid) in the total mass of the tape casting slurry.

[0021] Furthermore, the sintering aid is a mixture of 1 to 3 parts by mass of calcium carbonate and 1 to 3 parts by mass of silicon dioxide, or a mixture of 1 to 3 parts by mass of calcium oxide and 1 to 3 parts by mass of silicon dioxide.

[0022] Furthermore, the dispersant is selected from polyacrylic acid or ammonium polyacrylate.

[0023] Furthermore, the binder is selected from any one of polyvinyl alcohol, hydroxypropyl methylcellulose, methylcellulose, hydroxyethyl cellulose, and acrylic emulsion.

[0024] Furthermore, the plasticizer is selected from any one of polyethylene glycol, glycerol, and dibutyl phthalate, or a mixture of any two thereof.

[0025] Generally, the solvent is water.

[0026] Generally, in step S1 , the thickness of a single piece of ceramic green body is 40 μm to 60 μm.

[0027] Specifically, in step S2, the rotation-symmetric lamination process includes:

[0028] S21, arranging the ceramic green bodies in rows and rotating them in the same direction by 90 degrees in sequence;

[0029] S22, stacking two adjacent ceramic green sheets as a group;

[0030] S23, stacking the plurality of ceramic green sheets obtained after the first stacking for a second time to obtain a laminated body; wherein the edges of adjacent ceramic green sheets in the laminated body do not overlap, and the casting directions of adjacent ceramic green sheets are different.

[0031] Furthermore, in step S2, the number of ceramic green sheets is 4 or 6.

[0032] Furthermore, the steps of symmetrical lamination include:

[0033] S211, arranging four ceramic green sheets in a row and rotating them in the same direction by 90 degrees in sequence;

[0034] S221, stacking two adjacent ceramic green sheets as a group, with the stacking directions of the two groups of ceramic green sheets being symmetrical;

[0035] S231, stacking the two groups of ceramic green bodies obtained after the first stacking for a second time to obtain a laminated green body;

[0036] or,

[0037] S212, arranging six ceramic green sheets in a row and rotating them in the same direction by 90 degrees in sequence;

[0038] S222, stacking two adjacent ceramic green sheets as a group, wherein the stacking directions of the first and second groups of ceramic green sheets are symmetrical, and the stacking direction of the third group of ceramic green sheets is consistent with that of the second group of ceramic green sheets;

[0039] S232, stacking the three groups of ceramic green bodies obtained after the first stacking in sequence for a second time in the same direction to obtain a laminated green body.

[0040] Specifically, in step S3, the warm isostatic pressing procedure includes: heating to 50°C to 80°C and maintaining the temperature, pressurizing from 0 MPa to 20 MPa to 50 MPa and holding the pressure for 200s to 400s, and then pressurizing to 80 MPa to 120 MPa for a second time and holding the pressure for 750s to 1000s.

[0041] The use of a staged warm isostatic pressing operation helps multiple ceramic green sheets in the laminated body to be fully combined and formed under a lower pressure after one pressurization, so as to form a structure with better integrity before sintering.

[0042] Furthermore, the rate of the first pressurization is 3 MPa / min to 5 MPa / min, and the rate of the second pressurization is 6 MPa / min to 8 MPa / min.

[0043] Specifically, in step S3, the sintering procedure includes: heating to 150°C to 250°C at normal pressure, then heating to 400°C to 600°C for a second time at a reduced speed and keeping warm for 240min to 360min, and then heating to 1500°C to 1700°C for a third time and keeping warm for 7h to 10h.

[0044] Furthermore, the rate of the first heating is 5°C / min to 7°C / min, the rate of the second heating is 2°C / min to 4°C / min, and the rate of the third heating is 2°C / min to 5°C / min.

[0045] The above-mentioned anti-warping preparation method of the present invention, firstly, ensures that the edges of adjacent ceramic green sheets are not repeated and the corresponding casting directions before preparing the ceramic green sheets are not repeated through the rotation and stacking stacking method, and the bottom surface of the ceramic green sheet with a denser structure obtained during casting is located on the outer surface of the laminated body, thereby maximally adjusting the residual stress distribution inside the ceramic green sheet obtained after casting; secondly, the coordinated warm isostatic pressing and sintering processes are both processed by multi-stage procedures, which provides sufficient guarantee for the anti-warping of the laminated thin-sheet ceramic obtained after the final sintering, and solves the problems of sintering warping and low production output of laminated thin-sheet ceramics at low cost and high efficiency. The anti-warping preparation method also does not need to increase the solid content of the casting slurry. It only needs to control the solid content of the casting slurry at a conventional level to improve the sintering warping problem of the laminated thin-sheet ceramics. Compared with the solution of improving the warpage rate by increasing the solid content in the prior art, the lower solid content can also avoid the disadvantages of easy uneven dispersion and affecting the casting effect caused by high solid content. The low-warpage laminated ceramic provided by the present invention achieves an extremely low warpage level of at least 100% with a ratio less than the side length*0.1%. BRIEF DESCRIPTION OF THE DRAWINGS

[0046] Figure 1 2. This is a schematic diagram of a symmetrical stacking of ceramic green sheets according to Example 1 of the present invention;

[0047] Figure 2 2. Schematic diagram of secondary stacking of symmetrically stacked ceramic green sheets according to Example 1 of the present invention;

[0048] Figure 3 2. It is a schematic diagram of a symmetrical stacking of ceramic green bodies according to Example 2 of the present invention;

[0049] Figure 4 and Figure 5 Schematic diagram of secondary stacking of symmetrically stacked ceramic green bodies according to Example 2 of the present invention. DETAILED DESCRIPTION

[0050] For a better understanding of the present invention, the following examples are further illustrative of the present invention and are only used to explain the content of the present invention, but not to limit the present invention. All similar embodiments listed based on the present invention should fall within the scope of protection.

[0051] Example 1

[0052] This embodiment provides a method for preparing a warpage-resistant laminated ceramic sheet, which includes the following steps:

[0053] In the first step, 100 parts by weight of alumina powder, 1 part of calcium carbonate powder, 3 parts of silica powder, 50 parts of deionized water, and 1 part of polyacrylic acid were put into a ball mill and mixed by high-speed ball milling for 10 hours to obtain an alumina slurry.

[0054] In the second step, 10 parts of polyvinyl alcohol and 8 parts of polyethylene glycol were added to the alumina slurry, and the mixture was evenly stirred by ball milling to obtain a casting slurry with a solid content of 60%.

[0055] In the third step, the tape-casting slurry is tape-casted to form four ceramic blanks, which are then cut into ceramic green sheets with a thickness of 60 μm.

[0056] The fourth step is to symmetrically stack four ceramic green sheets to obtain a laminated body.

[0057] Specifically, first, four ceramic green sheets are arranged in a row and rotated 90 degrees in the same direction, that is, the 1# ceramic green sheet remains stationary, the 2# ceramic green sheet is rotated 90 degrees clockwise, the 3# ceramic green sheet is rotated 180 degrees clockwise, and the 4# ceramic green sheet is rotated 270 degrees clockwise; then, Figure 1 In the stacking direction shown, two adjacent ceramic green sheets are stacked to obtain two sets of ceramic green sheets; again, according to Figure 2 In the stacking direction shown, two groups of ceramic green bodies are stacked to obtain a laminated body.

[0058] In the above Figure 1 and Figure 2 In FIG, the direction of the arrow inside the ceramic green body indicates the casting direction in the third step. Figure 2 In the figure, the ceramic green body with the casting direction indicated by the dotted line is located at the bottom layer of the group, and the ceramic green body with the casting direction indicated by the solid line is located at the surface layer of the group.

[0059] The fifth step is to place the laminated green body into a warm isostatic press, first raise the temperature to 70°C and keep it warm, increase the pressure from 0 MPa to 40 MPa at a pressurization rate of 3.5 MPa / min to 4.5 MPa / min (with slight fluctuations during the period), maintain the pressure for 200 seconds, and then pressurize to 80 MPa at a pressurization rate of 6.6 MPa / min to 7.8 MPa / min (with slight fluctuations during the period), maintain the pressure for 950 seconds, and obtain an alumina ceramic green body.

[0060] In the sixth step, the obtained alumina ceramic body is placed in a vacuum pressure sintering furnace. Under normal pressure conditions, the temperature is first increased to 150°C at a heating rate of 5°C / min to 6.5°C / min (with slight fluctuations during the period), and then increased to 400°C for a second time at a heating rate of 2°C / min to 3.2°C / min (with slight fluctuations during the period), and kept warm for 260 minutes. Then, the temperature is increased to 1500°C for the third time at a heating rate of 2°C / min to 3°C / min (with slight fluctuations during the period), and kept warm for 10 hours to obtain alumina laminated thin film ceramics.

[0061] Example 2

[0062] This embodiment provides a method for preparing a warpage-resistant laminated ceramic sheet, which includes the following steps:

[0063] In the first step, 120 parts of alumina powder, 2 parts of calcium carbonate powder, 2 parts of silica powder, 44 parts of deionized water, and 1.5 parts of polyacrylic acid were put into a ball mill, and mixed by high-speed ball milling for 10 hours to obtain an alumina slurry.

[0064] In the second step, 12 parts of polyvinyl alcohol and 8 parts of polyethylene glycol were added to the alumina slurry, and the mixture was evenly mixed by ball milling to obtain a casting slurry with a solid content of 65%.

[0065] In the third step, the tape-casting slurry is tape-casted to form six ceramic blanks, which are then cut into ceramic green sheets with a thickness of 40 μm.

[0066] In the fourth step, six ceramic green sheets are symmetrically stacked to obtain a laminated body.

[0067] Specifically, first, six ceramic green sheets are arranged in a row and rotated 90 degrees in the same direction, that is, the 1# ceramic green sheet remains stationary, the 2# ceramic green sheet is rotated 90 degrees clockwise, the 3# ceramic green sheet is rotated 180 degrees clockwise, the 4# ceramic green sheet is rotated 270 degrees clockwise, the 5# ceramic green sheet is rotated 360 degrees clockwise, and the 6# ceramic green sheet is rotated 450 degrees clockwise; then, according to Figure 3 In the stacking direction shown, two adjacent ceramic green sheets are stacked to obtain three sets of ceramic green sheets; again, according to Figure 4 and Figure 5 In the stacking direction shown, three groups of ceramic green bodies are stacked in sequence in the same direction to obtain a laminated green body.

[0068] In the above Figures 3 to 5 In FIG, the direction of the arrow inside the ceramic green body indicates the casting direction in the third step. Figure 4 and Figure 5 In the figure, the ceramic green body whose casting direction is indicated by a dotted line is located in the lower layer of the group, and the ceramic green body whose casting direction is indicated by a solid line is located in the surface layer of the group.

[0069] The fifth step is to place the laminated green body into a warm isostatic press, first raise the temperature to 80°C and keep it warm, increase the pressure from 0 MPa to 40 MPa at a pressurization rate of 4 MPa / min to 5 MPa / min (with slight fluctuations during the period), maintain the pressure for 300 seconds, and then pressurize to 80 MPa at a pressurization rate of 7 MPa / min to 8 MPa / min (with slight fluctuations during the period), maintain the pressure for 800 seconds to obtain an alumina ceramic green body.

[0070] In the sixth step, the obtained alumina ceramic body is placed in a vacuum pressure sintering furnace. Under normal pressure conditions, the temperature is first increased to 150°C at a heating rate of 5.5°C / min to 6.3°C / min (with slight fluctuations during the period), and then the temperature is increased to 500°C for the second time at a heating rate of 2.5°C / min to 3.5°C / min (with slight fluctuations during the period), and kept warm for 300 minutes. Then the temperature is increased to 1700°C for the third time at a heating rate of 2°C / min, and kept warm for 9 hours to obtain alumina laminated thin film ceramics.

[0071] Example 3

[0072] In the description of Example 3, the similarities with Example 2 are not repeated here, and only the differences from Example 2 are described. The difference between the anti-warpage preparation method provided in Example 3 and that in Example 2 is that 3 parts of calcium oxide powder, 3 parts of silicon dioxide powder, 0.5 parts of ammonium polyacrylate, 8 parts of acrylic emulsion, 8 parts of polyethylene glycol and 53 parts of deionized water are used as raw materials for preparing the casting slurry; in the warm isostatic pressing procedure, the pressure is maintained for 200 seconds after the first pressurization and for 1000 seconds after the second pressurization; in the sintering procedure, the temperature is increased three times at a heating rate of 3°C / min to 3.5°C / min (with slight fluctuations during the period) and then maintained for 7 hours; the rest is referred to as described in Example 2 to obtain alumina laminated thin film ceramics.

[0073] Example 4

[0074] In the description of Example 4, the similarities with Example 1 are not repeated here, and only the differences from Example 1 are described. The difference between the anti-warping preparation method provided in Example 4 and that in Example 1 is that 100 parts of alumina powder, 3 parts of calcium carbonate powder, 3 parts of silica powder, 1.5 parts of ammonium polyacrylate, 14 parts of hydroxypropyl methylcellulose, 6 parts of glycerol and 45 parts of deionized water are used as raw materials for preparing the casting slurry, and the first high-speed ball milling mixing time is 12 hours; in the warm isostatic pressing procedure, the temperature is raised to 50°C and kept warm continuously, the pressure is applied to 20MPa once, and the pressure is maintained for 1000s after the second pressurization; in the sintering procedure, the temperature is raised to 600°C for the second time, and then the temperature is raised to 1600°C three times at a heating rate of 3.5°C / min to 4°C / min (with slight fluctuations during the period), and kept warm for 7 hours; the rest is as described in Example 1 to obtain alumina laminated thin film ceramics.

[0075] Example 5

[0076] In the description of Example 5, the similarities with Example 1 are not repeated here, and only the differences from Example 1 are described. The difference between the anti-warping preparation method provided in Example 5 and that in Example 1 is that 100 parts of alumina powder, 2 parts of calcium oxide, 4 parts of silicon dioxide, 12 parts of methyl cellulose, 6 parts of polyethylene glycol and 50 parts of deionized water are used as raw materials for preparing the casting slurry, and the first high-speed ball milling mixing time is 12 hours; in the warm isostatic pressing procedure, the pressure is applied to 50 MPa once and then maintained for 400 seconds, and the pressure is applied to 120 MPa twice and then maintained for 900 seconds; in the sintering procedure, the temperature is raised to 250°C at a heating rate of 6°C / min, and the temperature is raised twice and then maintained for 360 minutes; the rest is as described in Example 1 to obtain alumina laminated thin film ceramics.

[0077] Example 6

[0078] In the description of Example 6, the similarities with Example 2 are not repeated here, and only the differences from Example 2 are described. The difference between the anti-warping preparation method provided in Example 6 and that in Example 2 is that the raw materials for preparing the casting slurry include 110 parts of alumina powder, 3 parts of calcium carbonate powder, 1 part of silica powder, 50 parts of deionized water, 10 parts of hydroxypropyl methylcellulose, and 9 parts of dibutyl phthalate, and the first high-speed ball milling mixing time is 10 hours; in the warm isostatic pressing procedure, the pressure is maintained for 200 seconds after the first pressurization, and the pressure is maintained for 950 seconds after the second pressurization; in the sintering procedure, the temperature is raised to 600°C for the second time and maintained for 240 minutes, and then the temperature is raised three times at a heating rate of 4.5°C / min to 5°C / min (with slight fluctuations during the period) and maintained for 7 hours; the rest is as described in Example 2 to obtain alumina laminated thin film ceramics.

[0079] In order to demonstrate the effects of the lamination method, multi-stage warm isostatic pressing and sintering on the warpage rate of laminated ceramic sheets in the above-mentioned warpage-resistant preparation method of the present invention, several comparative experiments were conducted.

[0080] Comparative Example 1

[0081] In the description of Comparative Example 1, the similarities with Example 1 are omitted here; only the differences from Example 1 will be described. The warpage-resistant preparation method provided in Comparative Example 1 differs from that in Example 1 in that four ceramic green sheets are stacked in parallel, maintaining the same casting direction, to produce the ceramic green body; that is, they are neither rotated nor stacked. The remaining steps are similar to those described in Example 1, resulting in a first comparative alumina laminated ceramic sheet.

[0082] Comparative Example 2

[0083] In the description of Comparative Example 2, the similarities with Example 1 are omitted here; only the differences from Example 1 are described. The warpage-resistant preparation method provided in Comparative Example 2 differs from that in Example 1 in that the four ceramic green sheets are not rotated, but are stacked once, two by two, and then the two resulting sets are stacked a second time to obtain a ceramic green body. The remaining steps are similar to those described in Example 1, resulting in a second comparative alumina laminated ceramic sheet.

[0084] Comparative Example 3

[0085] In the description of Comparative Example 3, the similarities with Example 4 are omitted here; only the differences from Example 4 will be described. The warpage-resistant preparation method provided in Comparative Example 3 differs from that in Example 4 in that the four rotated ceramic green sheets are stacked in parallel, rather than facing each other. The remaining steps are similar to those described in Example 4, yielding a third comparative alumina laminated ceramic sheet.

[0086] Comparative Example 4

[0087] In the description of Comparative Example 4, the similarities with Example 1 are omitted here; only the differences from Example 1 are described. The warpage-resistant preparation method provided in Comparative Example 4 differs from that in Example 1 in that, after the temperature is raised to 70°C, the pressure is increased from 0 MPa to 80 MPa at a pressurization rate of 4 MPa / min and maintained at that pressure for 950 seconds to produce the alumina ceramic green body; in other words, a one-step warm isostatic pressing procedure is employed. The remaining procedures are the same as those described in Example 1, resulting in a fourth comparative alumina laminated ceramic sheet.

[0088] The performance of the laminated ceramic sheets prepared in each embodiment and comparative example was tested, as shown in Table 1 below:

[0089] Table 1 Performance test results of laminated ceramics of Examples and Comparative Examples

[0090]

[0091] As can be seen from Table 1, the laminated alumina thin sheet ceramics prepared in various embodiments of the present invention have high density, excellent thermal conductivity and bending strength, indicating that this special rotational lamination process does not damage the performance of the alumina laminated thin sheet ceramic substrate.

[0092] The warpage of the alumina laminated ceramic sheets produced in each example and comparative example was tested. Based on the square structure of the alumina laminated ceramic sheets, the warpage of the product was characterized by a ratio of warpage < side length * (0.2%, 0.15%, and 0.1%). The warpage test results are shown in Table 2 below.

[0093] Table 2 Warpage test results of alumina laminated ceramic sheets of the embodiment and comparative example

[0094]

[0095]

[0096] It can be seen from the warpage data in Table 2 that the alumina laminated thin sheet ceramics provided in the examples have extremely low warpage rates and achieve excellent anti-warpage effects, indicating that by improving the lamination method, warm isostatic pressing, and sintering processes, the residual stress distribution inside the ceramic green body after tape casting is effectively adjusted, thereby greatly reducing the adverse warpage caused by sintering.

[0097] In comparison, in Comparative Examples 1 and 2, since the ceramic green bodies were not rotated, the residual stresses in the various parts of the green bodies after lamination could not offset each other, and the subsequent sintering deformation was relatively large, resulting in severe warping of the obtained alumina laminated thin film ceramics.

[0098] Although the ceramic green body was rotated in Comparative Example 3, the parallel stacking would amplify the residual stress of each green body, causing stress concentration in the body. At the same time, it could not improve the adverse effects caused by the density difference between the upper and lower surfaces of the cast green body. The resulting alumina laminated thin sheet ceramic had a large warping degree and relatively poor performance.

[0099] By comparing Comparative Example 2 and Comparative Example 3, it can be seen that, in comparison, the non-rotation in Comparative Example 2 has a greater impact on the stress offset of the green body than the non-overlapping in Comparative Example 3, which results in the alumina laminated thin film ceramics in Comparative Example 2 being more severely warped than the alumina laminated thin film ceramics in Comparative Example 3.

[0100] In Comparative Example 4, compared with Example 1, the process of holding the pressure at 40 MPa for 200 seconds was not experienced during warm isostatic pressing. Instead, the pressure was increased to the final pressure in one step and then held. As a result, the forming effect of the ceramic green body (that is, the process of combining multiple ceramic green bodies to form a laminated green body) was poor, and the warping of the alumina laminated thin film ceramic obtained after sintering was increased.

[0101] It should be noted that the warpage of each embodiment in Table 2 above is limited only on the premise that the laminated thin-film ceramic is made into a square structure, but the present invention is not limited to this. When the laminated thin-film ceramic is made into other shapes, the warpage characterization method may change, but different characterization methods do not affect the warpage level of the laminated thin-film ceramic.

[0102] The embodiments used above are only for illustrating and explaining the contents of the present invention and do not constitute any special limitation to the present invention. Any form of modification made without departing from the basic concept of the present invention, as well as obvious modifications derived therefrom, fall within the scope of protection of the present invention.

Claims

1. A low-warpage laminated ceramic sheet, characterized in that: The warpage of the low-warpage laminated ceramic sheet is at least less than the side length*0.1%, and the proportion reaches 100%.

2. The low-warpage laminated ceramic sheet according to claim 1, characterized in that: The low warpage laminated ceramic sheet is formed by casting, laminating and sintering a casting slurry with a solid content of 60% to 65%; the casting slurry is a mixture of 100 to 120 parts by mass of aluminum oxide, 4 to 6 parts by mass of a sintering aid, 0.5 to 1.5 parts by mass of a dispersant, 8 to 14 parts by mass of a binder, 6 to 9 parts by mass of a plasticizer, and 40 to 60 parts by mass of a solvent.

3. The low warpage laminated ceramic sheet according to claim 2, characterized in that: The sintering aid is a mixture of 1 to 3 parts by mass of calcium carbonate and 1 to 3 parts by mass of silicon dioxide, or a mixture of 1 to 3 parts by mass of calcium oxide and 1 to 3 parts by mass of silicon dioxide; the dispersant is selected from polyacrylic acid or ammonium polyacrylate; the binder is selected from any one of polyvinyl alcohol, hydroxypropyl methylcellulose, methylcellulose, hydroxyethyl cellulose, and acrylic emulsion; the plasticizer is selected from at least one of polyethylene glycol, glycerol, and dibutyl phthalate; and the solvent is water.

4. A method for preparing a warpage-resistant laminated ceramic sheet, characterized in that: Includes steps: S1, preparing a tape casting slurry, and tape casting and cutting the tape casting slurry to obtain a ceramic green body; S2, performing a rotationally-symmetrical lamination process on the ceramic green sheets of an even number of sheets to obtain a laminated green body; S3, subjecting the laminated green body to multi-stage warm isostatic pressing and multi-stage sintering in sequence to obtain laminated thin-sheet ceramics.

5. The anti-warping preparation method according to claim 4, characterized in that: In step S1, the solid content of the casting slurry is 60% to 65%; the casting slurry is a mixture of 100 to 120 parts by mass of alumina, 4 to 6 parts by mass of a sintering aid, 0.5 to 1.5 parts by mass of a dispersant, 8 to 14 parts by mass of a binder, 6 to 9 parts by mass of a plasticizer, and 40 to 60 parts by mass of a solvent.

6. The anti-warping preparation method according to claim 4 or 5, characterized in that: In step S2, the steps of rotation-symmetric lamination processing include: S21, arranging an even number of the ceramic green sheets in rows, and rotating them in sequence in the same direction by 90°; S22, stacking two adjacent ceramic green sheets as a group; S23, stacking the plurality of ceramic green sheets obtained after the first stacking for a second time to obtain the laminated green body; wherein the edges of adjacent ceramic green sheets in the laminated green body do not overlap, and the casting directions of adjacent ceramic green sheets are different.

7. The anti-warping preparation method according to claim 6, characterized in that: The number of the ceramic green bodies is 4, and the steps of the rotationally-symmetrical lamination process include: S211, arranging four ceramic green sheets in a row, and rotating them in the same direction by 90 degrees in sequence; S221, stacking two adjacent ceramic green sheets as a group, and the stacking directions of the two groups of ceramic green sheets are symmetrical; S231, stacking the two groups of ceramic green bodies obtained after the first stacking for a second time to obtain the laminated green body.

8. The anti-warping preparation method according to claim 6, characterized in that: The number of the ceramic green bodies is 6, and the steps of the rotationally-symmetrical lamination process include: S212, arranging the six ceramic green sheets in a row, and rotating them in the same direction by 90° in sequence; S222, stacking two adjacent ceramic green sheets as a group, wherein the stacking directions of the first group of ceramic green sheets and the second group of ceramic green sheets are symmetrical, and the stacking directions of the third group of ceramic green sheets are consistent with those of the second group of ceramic green sheets; S232, stacking the three groups of ceramic green bodies obtained after the first stacking in sequence for a second time in the same direction to obtain the laminated green body.

9. The anti-warping preparation method according to claim 4, characterized in that: The single-piece thickness of the ceramic green body is 40 μm to 60 μm.

10. The anti-warping preparation method according to claim 4, characterized in that: In step S3, the warm isostatic pressing procedure includes: heating to 50°C-80°C and maintaining the temperature, pressurizing from 0 MPa to 20 MPa-50 MPa and maintaining the pressure for 200s-400s, and then pressurizing to 80 MPa-120 MPa for a second time and maintaining the pressure for 750s-1000s.

11. The anti-warping preparation method according to claim 4, characterized in that: In step S3, the sintering procedure includes: heating to 150°C-250°C at normal pressure, heating to 400°C-600°C for a second time at a reduced speed and keeping the temperature for 240min-360min, and heating to 1500°C-1700°C for a third time and keeping the temperature for 7h-10h.

Citation Information

Patent Citations

  • Preparation method of large-size aluminum nitride ceramic substrate

    CN107986794A

  • Preparation method of ceramic tube shell based on fiber alumina

    CN114634366A

  • Forming mold of ceramic substrate and cold isostatic pressing forming method thereof

    CN116551813A

  • Ceramic substrate and method for manufacturing same

    CN116828699A

  • Ceramic substrate and manufacturing method thereof

    CN118993712A

Cited By

  • Preparation method of high-thermal-conductivity Si3N4 ceramic substrate

    CN121735657A